La investigación sobre la formación inicial del profesor de Matemática en el marco de la XV CIAEM - León Gómez, Nelly (2019)
Mathematics teacher preparation is a field of research interest with multiple themes that are developed internationally. In the Inter-American Mathematics Education Conferences (IACMEs), Mathematics teacher preparation has had a strong presence including initial preparation as well as continuing education and professional development at the different educational levels of the participating countries. Here is a panoramic view of the current status of this issue based on the review of the approved works of IACME XV. It is a starting point towards reflection and contrast with global trends on the subject. Initial teacher preparation is emphasized. This document, with some minor modifications, served as the basis for the Thematic Session of IACME XV: “The initial and continuous preparation of mathematics teachers”.